The Impact of Customer Psychological Price on Audit Pricing in the Start-Up Company Market - Ding, Rui (Frontiers in Psychology, 2020)
Start-up companies are confronted with various risks and many uncertainties, and professional auditing can fully analyze start-up companies. In this way, both parties may maximize their interests through auditing the market activities. Based on the characteristics of start-up companies, this study explores the impact of customer psychological prices on audit pricing. The impact of customer psychological prices on audit pricing decisions was systematically analyzed from various angles, thereby determining whether it will affect the development of the product market. The results show that product market dominance reduces the agency costs between the owner and manager of the customer company. In other words, if the customers have greater control over the product market, they will have a lower business risk, and the auditor risk will be reduced accordingly, hence a lower audit fee. In the start-up company market, even if the financing dilemma restricts the survival and development of the company, customers still have psychological expectations for audit pricing. When their psychological price of products is different from the market price of products, it may affect the market advantage of products with lower audit fees, and further expands the previous research. In the market, customers also have certain psychological expectations for “auditing” products. Therefore, strengthening the relationship between auditors’ pricing and customers’ psychological prices has a positive effect on enhancing the competitiveness of product markets, which also increases the operating efficiency of start-up companies.